Hadith Learning Strategy in Early Childhood (Studies Multisite PAUD Qur'an Arraudhah and PAUD Integrated Shabwa Amanah) - Masriah Hariyani; Sulaiman Sulaiman; Erny Wahdini (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2022)
The purpose of the study to determine learning strategies of Hadith in PAUD. With qualitative descriptive approach and multisite design data collection through interviews, observation, documentation. The stages include reduction, presentation and conclusion. The results of research obtained by PAUD Qur'an Cahaya ArRaudhah and PAUD Terpadu Shabwa Trust Banjarbaru City are. 1) Planning before learning begins, carried out by teacher in collaboration with the PAUD head, Hadith learning planning is planned together with other lessons. The target of one week of hadith material adapting to abilities of early childhood aims to imitate the attitude of the Apostle and get used to having character like the character of the Apostle. 2) Implementation every day after reading prayers, reading Asmaul Husna, and short suras. The Hadith materials are cleanliness as part of faith, honest behavior, heaven under the feet of the mother, love, prohibition of anger, love of the homeland, prohibition of eating and drinking standing, giving gifts, praying and smiling. The learning methods are habituation, movement while singing, demonstration. Learning media uses objects around, illustrated paper media which there are colorful pictures and hadiths and media through cartoon videos. How to develop aspects of child development through Hadith learning is carried out classically and individually. 3) Assessment is carried out by group teachers and teachers who formed of teams with daily assessments and semester assessments.